Characteristics of chest high-resolution computed tomography in patients with anti-aminoacyl-tRNA synthetase antibody-positive interstitial lung disease - Mima, Masato; Sato, Seidai; Shinya, Takayoshi; Naito, Nobuhito; Shoji, Takatoshi; Harada, Saki; Suzue, Ryoko; Murakami, Kojin; Koyama, Kazuya; Nishioka, Yasuhiko (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Anti-aminoacyl-tRNA synthetase (ARS) antibodies form a condition called Antisynthetase syndrome (ASSD). While interstitial lung disease (ILD) is a particularly frequent manifestation of ASSD and is closely associated with morbidity and mortality, few studies have been conducted on its characteristics on high-resolution computed tomography (HRCT). In this study, we clarified the HRCT findings in patients with anti-ARS antibody-positive ILD (ARS-ILD).  Methods: The HRCT findings at the time of the ILD diagnosis in 24 ARS-ILD patients were retrospectively evaluated by 2 pulmonologists and one radiologist. We also assessed the clinical symptoms, physical examination findings, and laboratory data including the type of anti-ARS antibodies. For a further analysis, the data of patients were divided into two groups: the polymyositis (PM)/dermatomyositis (DM) group and the non-PM/DM group. Results: The ratio of men to women was almost 1:1. The median age at the time of the diagnosis was 53 years old. Anti-glycyl (anti-EJ) and anti-histidyl (anti-Jo-1) antibodies were more common than others. An analysis of the HRCT patterns of 23 ARS-ILD patients showed that the most common pattern was the nonspecific interstitial pneumonia (NSIP) pattern. The second most common pattern was the usual interstitial pneumonia (UIP) pattern. Between the PM/DM and non-PM/DM groups, no clear trends were noted in the age, sex ratio, proportion of HRCT patterns, or type of anti-ARS antibodies. Conclusions: This retrospective study demonstrated that ARS-ILD patients, regardless of myositis symptoms, most often showed the NSIP pattern on HRCT, as previously reported. However, unlike previous reports, the UIP pattern on HRCT was not rare.